EVALUASI KINERJA RUAS JALAN MALONDA KOTA PALU - Handayani, Lilis; Mashuri, Mashuri; Batti, Joy Fredi (MEKTEK, 2013)
Changes to the system activity around Palu Gulf Coast such as, the occupancy of hotel infrastructure, shopping centers and leisure facilities will impact on the Level of Service of Malonda street, in the present and the future. The aim of this study is to provide an alternative solutions that may be done to maintain level of services of Malonda street.The research data includes the data of traffic volume, travel time data of vehicle passing through the road segment is observed. Analysis and assessment level of services using Indonesian Highway Capacty Manual1997 and US-HCM 1994.The result found that the Level of Services of Malonda Street at this time is LOS C, while for the next 5 (five) years is LOS E. Solutions can be done to maintain the performance Malonda street is doing widening the carriageway width of 1.8 m.Keywords: Level of Services, Malonda Street, Palu city